Efficacy of Vapam fumigant against clubroot (Plasmodiophora brassicae) of canola. (25th February 2014) - Hwang, S. F.; Ahmed, H. U.; Zhou, Q.; Strelkov, S. E.; Gossen, B. D.; Peng, G.; Turnbull, G. D.
<x xml:space="preserve">Abstract</x> Clubroot, caused by Plasmodiophora brassicae, has become a serious threat to canola (Brassica napus) production in western Canada. Experiments were conducted under greenhouse and field conditions to assess the effect of Vapam fumigant (dithiocarbamate; sodium N‐methyldithiocarbamate) on primary and secondary infection by P. brassicae, clubroot severity, and growth parameters in canola. Preliminary trials showed a 12–16‐fold reduction in primary and secondary infection and clubroot severity at all of the Vapam application rates (0·4–1·6 mL L−1 soil) assessed. Vapam was also found to be effective in reducing clubroot severity and improving seed yield of canola under field conditions. Application of Vapam at soil moisture levels in the range of 10–30% (v:v) had a large effect on both disease severity and infection rates and plant growth parameters. The results suggest that Vapam can effectively reduce clubroot severity and may be useful for the treatment of transplant propagation beds in brassica vegetable production, and for the containment of small, localized clubroot infestations in commercial canola crops.